DEVELOPMENT ENCYCLOPEDIA BIOLOGY AS A REFERENCE FOR STUDENTS OF SENIOR HIGH SCHOOL - Etik Amalia (Universitas Islam Balitar, 2018)
The purpose of the development Encyclopedia biology learning tools and materials as a reference for students of Senior High School is knowing the quality of encyclopedia was developed based on the results of the assessment by a validator. This research include research development. The development model which used in this study is 4D model (Define, Design, Develop, dan Desseminate). The instrument assessement of the encyclopedia quality form of sheet check list by using Likert scale. The kind of data which took is validation from the experts, the response of theacher and students. The results of the expert assessement material, media experts, and linguists an average to 81,3% with very decent criteria. Biology teacher’s response is 84% and the student’s response is 82,06%. Based on the assessment of the validator and responses, so it can be concluded that these materials can be said to deserve be used for the students in the biology learning for Senior High School.